2011
DOI: 10.1002/jmv.22144
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the E2 and NS5A regions in patients infected with hepatitis C virus genotype 1a and their correlation with response to treatment

Abstract: Heterogeneity of subgenomic regions of hepatitis C virus (HCV) may be associated with response to interferon (IFN) therapy. The amino acid sequences of the PKR/eIF-2α phosphorylation homology domain (pePHD), IFN sensitivity determining region (ISDR), PKR binding domain (PKRBD), and variable region 3 (V3) were studied in 19 patients before and after 4 weeks of treatment. All patients were infected with HCV genotype 1a and were treated with pegylated-IFN and ribavirin. Thirteen patients achieved sustained viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
(28 reference statements)
2
12
0
Order By: Relevance
“…Consistent with other studies (6, 41), our findings showed that genotype 3 followed by genotypes 1 and 2 were dominant in responder subjects, and genotypes 1 and 3 were the most frequent genotypes in non-responder patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with other studies (6, 41), our findings showed that genotype 3 followed by genotypes 1 and 2 were dominant in responder subjects, and genotypes 1 and 3 were the most frequent genotypes in non-responder patients.…”
Section: Discussionsupporting
confidence: 93%
“…With the current treatment regimen, pegylated interferon (PEG-IFN) plus ribavirin, sustain virological response (SVR) is achieved in only 50% of infected individuals (4). A number of factors including age, alcohol consumption, viral genotype, duration of infection, and viral load have been assigned variable significances in determining the response to antiviral treatment (5, 6). However, the emerging field of immunogenetic has confirmed the significant role of heredity in host immune response to infections (7, 8).…”
Section: Introductionmentioning
confidence: 99%
“…Sequence variation of NS5A ISDR received considerable attention as a determinant of IFN resistance, mainly for Japanese genotype 1b isolates (67,68). However, other studies, including a study of patients with viral breakthrough during IFN treatment (61), suggested that sequence variation in other NS5A regions is associated with IFN treatment response (7,8,69). Of note, previously developed JFH1-based recombinants with 1b(J4) NS5A with and without sensitive-type ISDR mutations (46) responded similarly to IFN-␣ in experiments similar to those shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported that HCV-E2-PePHD is a highly conserved region [23,24,[27][28][29][30][31][32][33][34][35], but none of them described these results in patients coinfected with HIV. Gaudy et al [26] found a high degree of conservation of HCV-E2-PePHD in monoinfected patients with genotype 1b and no association between HCV-E2-PePHD mutations and response to treatment, while Yahoo et al [34] reported high amino acid conservation in HCV-1a at four weeks of treatment.…”
Section: Discussionmentioning
confidence: 92%
“…Gaudy et al [26] found a high degree of conservation of HCV-E2-PePHD in monoinfected patients with genotype 1b and no association between HCV-E2-PePHD mutations and response to treatment, while Yahoo et al [34] reported high amino acid conservation in HCV-1a at four weeks of treatment. The effect of HIV infection on PEG-IFN?RBV therapy outcome could produce changes in T-cell subsets.…”
Section: Discussionmentioning
confidence: 97%